An Overview and Future Perspectives of Aluminum Batteries. Issue 35 (30th June 2016) - Elia, Giuseppe Antonio; Marquardt, Krystan; Hoeppner, Katrin; Fantini, Sebastien; Lin, Rongying; Knipping, Etienne; Peters, Willi; Drillet, Jean‐Francois; Passerini, Stefano; Hahn, Robert
Abstract : A critical overview of the latest developments in the aluminum battery technologies is reported. The substitution of lithium with alternative metal anodes characterized by lower cost and higher abundance is nowadays one of the most widely explored paths to reduce the cost of electrochemical storage systems and enable long‐term sustainability. Aluminum based secondary batteries could be a viable alternative to the present Li‐ion technology because of their high volumetric capacity (8040 mAh cm −3 for Al vs 2046 mAh cm −3 for Li). Additionally, the low cost aluminum makes these batteries appealing for large‐scale electrical energy storage. Here, we describe the evolution of the various aluminum systems, starting from those based on aqueous electrolytes to, in more details, those based on non‐aqueous electrolytes. Particular attention has been dedicated to the latest development of electrolytic media characterized by low reactivity towards other cell components. The attention is then focused on electrode materials enabling the reversible aluminum intercalation‐deintercalation process. Finally, we touch on the topic of high‐capacity aluminum‐sulfur batteries, attempting to forecast their chances to reach the status of practical energy storage systems. Abstract : An overview of battery technologies employing aluminum metal anodes is reported, which are being considered as a viable alternative to Li‐ion technology thanks to aluminum abundance, low cost and high volumetric capacity (8040 mA h cm −3 for Al vs 2046 mA h cm −3 for Li).